2014
DOI: 10.1149/2.0021411jes
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Avert Electrochemical Shock and Their Demonstration in Spinels

Abstract: We demonstrate that extensive electrochemical shock-electrochemical cycling induced fracture-occurs due to coherency stresses arising from first order cubic-to-cubic phase transformations in the spinels LiMn 2 O 4 and LiMn 1.5 Ni 0.5 O 4 . Electrochemical shock occurs despite the isotropy of the shape changes in these materials. This electrochemical shock mechanism is strongly sensitive to particle size; for LiMn 2 O 4 and LiMn 1.5 Ni 0.5 O 4 , fracture can be averted with particle sizes smaller than ∼1 μm. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
(59 reference statements)
1
18
0
Order By: Relevance
“…In a previous study, 41 we demonstrated that we could induce fracture and associated acoustic emissions in LMO/Li cells by temporarily cycling at higher C-rates (current values denoted with respect to 1C, or the current required to discharge the cell in one hour) within the range 0 < X < 1 (4 V). That observation was consistent with the C-rate dependent "electrochemical shock" concept developed in detail by Woodford et al [42][43][44][45] However, their simulation results indicated that such diffusioninduced stress was small when compared with stresses caused by the cubic-cubic spinel phase transformation occurring in the 0 < X < 1 range; 44 the transformation stresses in the cubic-tetragonal regime are larger still. In the present work, we deliberately created controlled fracture events via the cubic-tetragonal transformation at 1 < X < 2, using LMO/Li half-cells.…”
supporting
confidence: 86%
“…In a previous study, 41 we demonstrated that we could induce fracture and associated acoustic emissions in LMO/Li cells by temporarily cycling at higher C-rates (current values denoted with respect to 1C, or the current required to discharge the cell in one hour) within the range 0 < X < 1 (4 V). That observation was consistent with the C-rate dependent "electrochemical shock" concept developed in detail by Woodford et al [42][43][44][45] However, their simulation results indicated that such diffusioninduced stress was small when compared with stresses caused by the cubic-cubic spinel phase transformation occurring in the 0 < X < 1 range; 44 the transformation stresses in the cubic-tetragonal regime are larger still. In the present work, we deliberately created controlled fracture events via the cubic-tetragonal transformation at 1 < X < 2, using LMO/Li half-cells.…”
supporting
confidence: 86%
“…[23][24][25][26][27] This phenomenon has been termed ''electrochemical shock'' in analogy to the thermal shock of brittle materials, which exhibits similar dependences on crystalline properties and microstructure. [28][29][30][31][32] Capacity fade and impedance growth in various lithium ion intercalation materials have been correlated to post-cycling observations of mechanical fracture. 24,26,27,33 Acoustic emission from electrochemical shock has also been directly recorded during charging and discharging.…”
Section: Txm Observations Of 3d Microstructural Evolutionmentioning
confidence: 99%
“…24,26,27,33 Acoustic emission from electrochemical shock has also been directly recorded during charging and discharging. [28][29][30][31][32][34][35][36] Here, TXM was used to non-destructively generate 3D tomographs of the single particles at different states of charge, which we correlate with the electrochemical measurements. Individual NMC333 and NCA single particles having B10 mm diameter were charged at C/3 rate to 3.9 V, 4.1 V, and 4.5 V, respectively.…”
Section: Txm Observations Of 3d Microstructural Evolutionmentioning
confidence: 99%
“…[17][18][19][20][21] In some cases, the macroscopic strain can be exploited as an actuator. [29][30][31][32] While there have been efforts in ultrasonic imaging of full cells, they have focused on the examination of irreversible failure through delamination and cracking. [29][30][31][32] While there have been efforts in ultrasonic imaging of full cells, they have focused on the examination of irreversible failure through delamination and cracking.…”
Section: Introductionmentioning
confidence: 99%